The Effect of Digital Financial Inclusion, MSME Productivity, and Regional Investment on Economic Growth in Malang Regency - Syamsul Huda (International Journal of Business and Quality Research, 2026)
This study examines the effects of digital financial inclusion, MSME productivity, and regional investment on economic growth in Malang Regency. Malang Regency was selected because it is a large regency with a diverse local economy, including manufacturing, agriculture, trade, tourism, and subdistrict-based micro and small enterprises. Regional economic digitalization is increasingly relevant because digital payments, fintech-based financial services, and MSME digital transformation can expand market access, reduce transaction costs, and promote more inclusive growth. This study applies an explanatory quantitative approach using a subdistrict-year panel design covering 33 subdistricts from 2019 to 2024, yielding 198 observations. Economic growth is proxied by a local economic growth index, digital financial inclusion by an index of digital financial service usage, MSME productivity by an index of turnover and output per worker, and regional investment by realized domestic and foreign investment. Multiple linear regression is employed after classical assumption tests. The simulated estimation results indicate that digital financial inclusion, MSME productivity, and regional investment positively and significantly influence economic growth. The adjusted R-squared value is 0.582, suggesting that the model explains 58.2 percent of the variation in local economic growth. Digital financial inclusion shows the strongest standardized effect, followed by regional investment and MSME productivity. The findings emphasize that inclusive regional growth requires an integrated policy combining digital finance expansion, MSME productivity upgrading, and productive investment acceleration